SOME DISODERS OF SEX DEVELOPMENT DIAGNOSED AT VIETDUC UNIVERSITY HOSPITAL FROM 2015 TO 2022 (Vietnam Journal of Community Medicine, 2022)
Backgroud: Disorders of sex development (DSDs) are a group of diseases caused by manydifferent causes, including DSDs due to anormal stage of sex organ differentiation andhormon synthesis disorders. Objectives: All patients diagnosed DSDs at Vietduc universityhospital from 2015 to 2022. Materials and method: Cross-sectional descriptive study.Results: 53 patients with DSDs include 25 patients with 5α-reductase type 2 deficiency,15 patients with congenital adrenal hyperplasia, 3 patients with androgen insensitivitysyndrome, 5 patient with complete gonadal dysgenesis, 1 patient with MRKH syndrome, 4patients with Ovotesticular. Conclusions: At Vietduc university hospital, we are diagnosedsome causes DSDs. In woman, DSDs most common were congenital adrenal hyperplasia,Mayer Rokitansky Kuster Hauser syndrome was rare in 46,XX patient. Enzyme 5α-reductasetype 2 deficiency, androgen insensitivity syndrome cause DSDs in man with pure 46,XY.Ovotesticular and complete gonadal dysgenesis cause many cases DSDs both men andwomen.
Keywords: Disorders of sex development, 5α-reductase type 2 deficiency, congenital adrenal hyperplasia, androgen insensitivity syndrome.